Antracologia e megalitismo na região Corgo/Tua (NE Portugal) : as mamoas da Alagoa e do Castelo - Figueiral, Isabel (Portvgalia : Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da FLUP, 2018)
Charcoal analysis results from two megalithic monuments, situated in north-eastern Portugal, are presented. The abundance of heathers, light demanding plants, is particularly striking. This contrasts with local present-day vegetation, and testifies to the existence of open areas, devoid of an important arboreal cover. The identification of Pinus tipo sylvestris and Taxus baccata, nearly extinct in Portugal, is also noted.